DESCRIPTION OF TEACHERS’ TEACHING PATTERNS IN PLAYGROUPS AND KINDERGARTENS - Vanessa Chavelita; Raja Oloan Tumanggor (Ikatan Dosen Menulis, 2026)
Early Childhood Education (ECE) plays an important role in supporting children's growth and development during the golden age period. In the learning process, teachers have a crucial role in planning, implementing, and evaluating learning activities that are appropriate to children's developmental characteristics. This study aimed to describe the teaching patterns of teachers in Playgroup and Kindergarten settings. A qualitative approach was employed using an in-depth interview method involving two early childhood teachers who had experience teaching at both Playgroup and Kindergarten levels. The findings revealed that learning plans were developed based on themes determined by the school, while their implementation remained flexible and was adjusted to children's interests, needs, and daily conditions. Learning activities in ECE were generally carried out through play-based approaches, including gross motor activities, fine motor activities, circle time, singing, and dancing. Teachers also utilized various learning media, such as flashcards, concrete objects, motor skill equipment, pictures, and videos to support children's learning experiences. Furthermore, positive teacher-child interactions were identified as an essential factor in creating a comfortable and enjoyable learning environment. Learning evaluation was conducted through observation, anecdotal records, and children's work portfolios. The study also found differences in teaching patterns between Playgroup and Kindergarten levels, particularly in terms of learning objectives, children's independence, and the complexity of learning materials. In addition, teachers faced several challenges, including maintaining children's attention, developing appropriate learning objectives, and adapting activities to children's developmental needs. The study concludes that teaching patterns in Early Childhood Education should be adjusted to the developmental characteristics of young children. Teachers serve not only as instructors but also as facilitators, companions, and guides who support children's development through meaningful and enjoyable learning experiences